Incidence of Infection among Subjects with Seroconversion - Young Jung Kim; Sun-Young Lee; Jeong Hwan Kim; In-Kyung Sung; Hyung Seok Park (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims: Helicobacter pylori (H. pylori) seroconversion may occur during screening for gastric cancer. Our study aimed to assess the number of seroconverted subjects with H. pylori and their results in follow-up tests. Methods: Data were consecutively collected on subjects who were H. pylori-seronegative and presented for gastric cancer screening. Subjects who were followed up using the same serology test and pepsinogen (PG) assays on the day of endoscopy were included in the study. Results: During the follow-up of 57.7±21.4 months, 61 (15.0%) of 407 seronegative subjects showed seroconversion. H. pylori infection was detected in six (9.8%) of 61 seroconverted subjects. A diffuse red fundal appearance, with a significant increase in the Kyoto classification scores for gastritis, was observed in the infected subjects (p<0.001). Compared to the false-seropositive subjects, infected subjects showed higher serology titers (p<0.001) and PG II levels (p<0.001) and lower PG I/II ratios (p=0.002), in the follow-up tests. Conclusions: Seroconversion occurred in 3.3% of seronegative subjects per year; however, only 9.8% had H. pylori infection. The majority (90.2%) of the seroconverted subjects showed false seropositivity without significant changes in the follow-up test results. The diffuse red fundal appearance could be an indicator of H. pylori infection.